Landscapes. - Michel, Emile, 1828-1909 (Temporis collection., 2012)
Although considered a minor genre for a long time, the art of landscape has risen above its forebears - religious and historic painting - to become a genre of its own. Giorgione in Italy, the Brueghels of the Flemish School, Claude Lorrain and Poussain of the French School, the Dutch landscape painters and Turner and Constable of England are just a few of the great landscapists who have left their indelible mark on the history of landscape and the art of painting as a whole. After serving for a long time as a backdrop for paintings and as a skill-practising exercise for artists, nature came to.